Development of Pragmatic Competence through Translanguaging among English Language Learners: ELT Teachers’ Perspectives - Iqbal, Sajid; Maqbool, Saira (Pakistan Languages and Humanities Review, 2025)
This study qualitatively explores the role of translanguaging in developing pragmatic competence among English language learners at higher secondary level in Punjab. The objective of this study was to analyze how translanguaging helps in developing pragmatic competence among English language learners at higher secondary school level. Using purposive sampling technique, twelve ELT teachers were interviewed for collection of qualitative data. The data was then analyzed thematically. The findings reveal that translanguaging is an effective pedagogical strategy for ELT teachers to enhance pragmatic understanding of learners by connecting English expressions with their native language and cultural backgrounds. The findings also reveal that translanguaging helps English language learners to develop their pragmatic competence by reducing foreign language anxiety and developing their confidence. The study recommends translanguaging as an effective pedagogical strategy in bridging linguistic and pragmatic gaps and advocates its integration into teacher training and curriculum to enrich ESL pedagogy in Punjab.